Perancangan Sistem Informasi Deteksi Kegagalan Koperasi Di Tingkat Provinsi Berbasis Algoritma C4.5 - Anik Andriani (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
Cooperative is one of actors in Indonesian economywhich is expected to be a cornerstone of Indonesian economy. Based on statistical data on the site of Ministry of Cooperatives and Small and Medium, many cooperative at provincial level have failed. One attempt to be able to reduce failure rate of cooperatives at provincial level is that there needs an effective and efficient guidance to know reasons of failure cooperative, so the coaching focused on the reasons of failure. The purpose of this research is building cooperative failure detection system based on rule of classification results from cooperative dataset using C4.5 algorithm. The stage of system development implemented Waterfall software development, while Black Box Testing Method was used as system testing for measuring whether system was able to run well or not. The result shows that information system of failure detection cooperative at provincial level can detect cooperative failure and provide information of most influential factor in that failure.